Misapplied trust funds and mortgage loans - TAN, Ruo Yu (Institutional Knowledge at Singapore Management University, 2017)
Where trust monies are used in breach of trust to pay for the deposit for a property, the courts have held that any mortgage loan which was used to fund the purchase does not count as the trustee's contribution to the purchase price for the purpose of determining the trustee's and the beneficiary's respective beneficial ownership in the property. This article considers two issues. First, if trust monies are used only after the trustee has paid for the deposit using his own money, are the loan monies obtained by the trustee under the mortgage still liable to be discounted as his contribution? Second, does it make a difference in the assessment whether the beneficiary is seeking to trace the misapplied trust funds into the sale proceeds or an account of profits which the trustee obtained in breach of the no-profit rule?